Zirconium-based photoelectrodes for the production of solar fuel - Amer, Ahmad Waleed (AUC Knowledge Fountain, 2015)
With global climate change becoming a chronic situation, humanity needs to come up with efficient, sustainable, and clean alternative energy sources that can truly create markets capable of competing with the fossil fuel industry. Being one of the fundamental constituents of the greater part of the planet, Hydrogen emerges as one of the best alternative fuels, offering comparable –or higher- energy levels, as well as cleaner combustion results, when compared with our everyday sources of energy. Also, water is both the primary source and resultant, which means full sustainability. The process of producing Hydrogen gas, however, is not as giving. Huge amounts of energy are consumed daily to produce amounts of Hydrogen gas that can barely cover the currently-low market demand. Thus, the need to develop more efficient Hydrogen production systems is dire. Being the gigantic nuclear fusion reactor it is, the Sun supplies our planet with more energy per day than all of industrial energy sources combined. Harvesting such energy is made available by pyroelectric as well as semiconducting materials. With the invention of the transistor, the world’s focus on the latter materials increased greatly, and huge amounts of research has been taken out ever since. It is now a global ultimatum to develop semiconducting systems that can efficiently convert the energy of the Sun to electrical energy to be used in the electrolysis of water for the production of Hydrogen gas. In this thesis, an Earth-abundant material, Zirconium, was used to develop semiconducting electrodes for that exact purpose. Because nanostructuring offers new properties un-attainable at the macro scale, in the first part of this thesis, a comprehensive study was taken out to develop protocols for the synthesis of semiconducting Zirconium Oxide nanotubes (NTs) with different lengths, diameters, wall thicknesses, and morphologies. It was shown that, using the cheap electrochemical anodization method, Zirconia NTs with hexagonal as well as circular cross sections were synthesized, depending on the concentrations of water and etchant in the electrochemical bath. The control of length, diameter, and wall thickness was also attained through controlling the applied potential, anodization time, as well as the solvent composition of the electrolyte. With the aims of using these NTs in solar water splitting, the smallest wall thickness, as well as the best structure, were the main drives behind choosing the optimum electrolyte-potential-time combination for NT synthesis. Thus, the synthesis of semiconducting, widely stable Zirconia NTs was successful. Zirconia NTs are wide band gap semiconductors, limiting their optical absorption to the Ultra Violet region (<10%) of the solar spectrum. Thus, their use in solar water splitting proves to be inefficient. It was, thus, the aim of the second part of this thesis to cheaply modify the synthesized nanostructured electrodes. Atomic Layer Deposition (ALD) was used to deposit very thin layers of Zirconium Nitride, another Earth-abundant compound, to drive Oxygen/Nitrogen diffusion, and eventually attain an oxynitride layer on the surface of the oxide NTs. This so-called Zirconium Oxynitride layer is known to have visible-light absorption characteristics, which would greatly increase the efficiency of the resulting photoanodes. Indeed, the chemical composition was proven to be a mixed oxide-nitride layer through X-ray Photoelectron Core and Valence Band Spectroscopy. UV-Vis and Tauc optical analysis proved the shift in the optical band gap of the oxide NTs from 3.8 to 2.4 eV. Photoelectrochemical analysis showed a higher catalytic activity for the composite photoanodes as compared to the bare oxide NTs. Electrochemical Impedance Spectroscopy showed that the increase in photogenerated carriers, as well as the decrease in the hole potential barrier at the photoelectrode/electrolyte interface in the composite electrodes, may be the main reasons behind the performance enhancement witnessed in these electrodes.